Math

posted by .

Find (fog)(2) and (gof)(-2)

f(x)=Square root of 4-x; g(x)=1-3x^2

Show work.

• Math -

f(g) = sqrt(4-g) = sqrt(4-(1-3x^2)) = sqrt(3+3x^2)
f(g(2)) = sqrt(3+12) = sqrt(15)

or, g(2) = 1-12 = -11
f(-11) = sqrt(4+11) = sqrt(15)

do g(f) the same way.

Similar Questions

1. Calculus

Hi there, I need help with composition of functions. I need to find fog, gof, gog, and fof and their domains for the following: f(x) = square root of 2x +3 g(x) = x^2 + 1 if someone can help me asap that would be so great!
2. Composite Functions

f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (gof)(x) (fog)(-1)
3. college algebra

1. answer the following for the given quadratic function f(x)=x^2+10x-11 a.what is the vertex (h,k) of f?
4. math

find the functions f&g so that fog = H H(x)=squre root x^2+8 please show work
5. pre calculus

1.) If h(x)= (fog)(x) and h(x) = 3 over the square root of x+3 , find g(x) if f(x)= 3 over the square root of x+2. my answer is x+1. Am I right?
6. math

Nakim simplified 3 times the square root of 2x plus x times the square root of 8x minus 5 times the square root of 18x and got -10x times the square root of 2x for an answer. Part 1: Using complete sentences, explain what Nakim did …